Comparision of Cardiovascular Risk Factors and Carotis Intima Media Thickness in Patients with Single Valve and Double Valve Calcifications (Annals of Medical Research, 2021)
None
Keywords: Aortic Valve Calcification; Mitral Annular Calcification; Carotis Intima Media Thickness; Cardiovascular Risk Factors.